SERUM VITAMIN D LEVELS IN COVID PNEUMONIA PATIENTS ADMITTED TO ICU: CORRELATION WITH SEVERITY AND OUTCOME - Dr Sobhya Karamullah; Dr Serwat Anjum; Dr Ghaffar Dars; Dr Sanobar Baloch (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The global landscape transformed with the emergence of COVID-19 in 2019, a disease profoundly impacting the respiratory system and cascading into multi-organ involvement. Amidst the quest for effective preventive and therapeutic measures, Vitamin D has garnered attention due to its historical role in immunomodulation, particularly in respiratory viral infections. Objectives: • Assess serum Vitamin D levels in patients with severe and critical COVID-19 pneumonia admitted to the ICU. • Establish a relationship between low Vitamin D levels and disease severity as well as clinical outcomes, including hospital stay, discharge, and mortality. Setting: The study was conducted within the COVID-19 and medical ICUs at Liaquat University Hospital (LUH), Hyderabad. Study Period: Hospital records from August 20, 2020, to January 20, 2021, were retrospectively collected. Study Design: A retrospective cross-sectional analysis was employed. Methodology: A cohort of 186 patients (both genders, aged 25-75) admitted to the ICU for critical COVID-19 pneumonia underwent evaluation. Patient demographics, comorbidities, pre-ICU illness duration, laboratory data (including Vitamin D levels), and imaging records were analyzed using SPSS version 22. Results: Among the 186 patients, 62.4% were male and 37.6% were female. Notably, 83.3% exhibited Vitamin D deficiency, while 15% showed insufficiency. Gender disparities were observed, with males displaying greater susceptibility (p < 0.05). Vitamin D deficiency correlated positively with prolonged hospitalization, mechanical ventilation necessity, and mortality. Gender emerged as a confounding factor, as females displayed higher insufficiency rates (22.8% vs. 10%) and males exhibited greater deficiency rates (85% vs. 75%), with age and comorbidities not exerting a similar impact. Conclusion: COVID-19 pneumonia patients admitted to the ICU exhibited notably low Vitamin D levels, aligning with increased morbidity and mortality rates. This underscores the significance of addressing Vitamin D status in the management of severe COVID-19 cases.